Analysis of Language Politeness Principles in Lifeboy Product Advertisements - Sri Wulandari; Ismey Adinda Khairani; Suci Prantina; Nabila Ariska; Juli Yani (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study investigates the implementation of politeness principles in Lifebuoy product advertisements, focusing on how linguistic politeness contributes to effective and ethical communication. Politeness in language plays a vital role in advertising, as it seeks to attract consumer interest while avoiding offense, ambiguity, or miscommunication. Employing a qualitative descriptive methodology and a discourse analysis approach, this research delves into the strategic use of politeness elements, such as goodwill, message clarity, respect for the audience, and careful word choice, in Lifebuoy advertisements. The analysis highlights how these advertisements align with politeness principles by ensuring relevance, maintaining clarity, and employing persuasive yet respectful and culturally sensitive language. Additionally, the study identifies how these strategies foster consumer trust, reinforce brand credibility, and contribute to a positive product image. By balancing persuasive techniques with ethical communication, Lifebuoy advertisements successfully convey their messages while respecting the audience's values and expectations, offering insights into the broader implications of politeness in advertising. This research underscores the importance of integrating linguistic politeness in marketing strategies to enhance consumer engagement and brand perception.